Species Diversity, Distribution and Relative Abundance of Avifuana in the Mangrove of Karamjal Forest Station, Sundarbans (Bangladesh Journal of Zoology, 2020)
Study on bird species diversity, distribution and relative abundance is important for conservation efforts in local and national scale. However, bird diversity, distribution and relative abundance are little known in Karamjal Forest Station, Sundarbans. Ecological appraisal of bird species diversity, distribution and relative abundance of the avifauna of the Karamjal Forest Station were conducted from June 2015 to April 2016. A total of 156 bird species was recorded during the study period. Of which, one was globally Critically Endangered, Gyps bengalensis and two were Near Threatened i.e., Gyps himalayensis and Lusciniapectardens. The distribution of bird among habitat type was significantly different (f =22.069, p